Art and Illusionists - Wade, Nicholas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
We delight in using our eyes, particularly when puzzling over pictures. Art and illusionists is a celebration of pictures and the multiple modes of manipulating them to produce illusory worlds on flat surfaces. This has proved fascinating to humankind since the dawning of depiction. Art and illusionists is also a celebration of the ways we see pictures, and of our ability to distil meaning from arrays of contours and colours. Pictures are not only a source of fascination for artists, who produce them, but also for scientists, who analyse the perceptual effects they induce. Illusions provide the glue to cement the art and science of vision. Painters plumb the art of observation itself whereas scientists peer into the processes of perception. Both visual artists and scientists have produced patterns that perplex our perceptions and present us with puzzles that we are pleased to peruse. Art and illusionists presents these two poles of pictorial representation as well as presenting novel 'perceptual portraits' of the artists and scientists who have augmented the art of illusion. The reader can experience the paradoxes of pictures as well as producing their own by using the stereoscopic glasses enclosed and the transparent overlay for making dynamic moiré patterns.
Introduction -- Perspective Paradoxes -- Trompe l'oeil -- Mosaics and Tiling -- Impossible Figures -- Surrealism -- Geometrical Optical Illusions -- Ambiguity -- Hidden Images -- Word and Image -- Colour -- Contrast -- Faces -- Scintillation and Apparent Motion -- Moiré and Motion -- Stereoscopic Vision.
Keywords: Signal processing; Engineering; Life sciences; Social sciences; Humanities; Science; Mathematics; Signal, Speech and Image Processing; Technology and Engineering; Life Sciences; Humanities and Social Sciences; Physical Sciences; Mathematics and Computing